2013
DOI: 10.3109/17518423.2013.809811
|View full text |Cite
|
Sign up to set email alerts
|

iPad-presented social stories for young children with autism

Abstract: Overall, this study builds on existing research that supports social stories as a promising practice. Further research into the use of iPad-presented social stories, particularly for children of varying ages, abilities, and learning styles is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…However, only 29.8% families had used the booklets regularly, and a portion of parents reported that they did not have time to show the booklets to their children. In the previous studies, the frequency of using a social story was also inconsistent, for instance, two to three times per week, 4 days a week, or at least 25 hr per week [Crozier & Tincani, ; Hsu et al, ; C. M. More et al, ; Raver et al, ; Vandermeer et al, ]. Regression analysis revealed that the frequency of social story reading was not significantly associated with the efficacy of social story intervention in training toothbrushing skills.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, only 29.8% families had used the booklets regularly, and a portion of parents reported that they did not have time to show the booklets to their children. In the previous studies, the frequency of using a social story was also inconsistent, for instance, two to three times per week, 4 days a week, or at least 25 hr per week [Crozier & Tincani, ; Hsu et al, ; C. M. More et al, ; Raver et al, ; Vandermeer et al, ]. Regression analysis revealed that the frequency of social story reading was not significantly associated with the efficacy of social story intervention in training toothbrushing skills.…”
Section: Discussionmentioning
confidence: 95%
“…Social stories can be used to emphasize a specific skill that a child needs to improve [Benish & Bramlett, ]. In the past decades, social story intervention had been applied to promote peer interactions (inviting friends, explaining an event to peers, sharing toys, playing turn‐taking), diminish stereotypical behaviors, reduce interruptive behaviors, and establish self‐regulation behaviors among preschool children [Agosta et al, ; Benish & Bramlett, ; Chan & O'Reilly, ; Crozier & Tincani, ; Hsu, Hammond, & Ingalls, ; Kassardjian et al, ; Kuoch & Mirenda, ; Litras, Moore, & Anderson, ; C. M. More et al, ; Thompson & Johnston, ; Vandermeer, Beamish, Milford, & Lang, ]. Increment of the expected behaviors and/or reduction in the unfavorable behaviors were observed in most of the above studies, indicating that social story intervention could serve as a potential approach for behavior management among young children.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the studies evaluated in this category in terms of targeted skills demonstrated that studying skills (Hourcade, Bullock-Rest, & Hansen, 2012) and teaching social stories were targeted (Vandermeer, Beamish, Milford, & Lang, 2015). While Hourcade et al (2012) conducted their study as a case study, Vandermeer et al (2015) utilized the multiple baseline model, one of the single-subject models.…”
Section: Use Of Portable Smart Devices For Teaching Communication Skimentioning
confidence: 99%
“…While Hourcade et al (2012) conducted their study as a case study, Vandermeer et al (2015) utilized the multiple baseline model, one of the single-subject models. Reviewing the applications used in these studies indicated that Hourcade et al (2012) utilized the Python-Based application in their study, while Stories2Learn application was used in Vandermeer et al's (2015) study.…”
Section: Use Of Portable Smart Devices For Teaching Communication Skimentioning
confidence: 99%
“…The use of digital technology to boost learning outcomes for students with diverse needs has been well documented [1]. More recently, findings from iPad use at home and at school by children with disabilities, particularly those on the autism spectrum, has yielded positive outcomes [2,3,4,5]. For these reasons, Griffith University special education staff collaborated with an industry partner, CHI.L.D Association (Let's Talk Developmental Hub, http://www.letstalk.org.au/child-assoc.html) in Brisbane Australia to apply for nongovernment funding through Ian Potter Foundation (http://www.ianpotter.org.au/) to undertake a home-based intervention study in which preservice teachers partnered with families of young children with communication difficulties.…”
Section: Introductionmentioning
confidence: 99%